Endoplasmic reticulum associated degradation preserves neurons viability by maintaining endoplasmic reticulum homeostasis - Wu, Shuangchan; Liu, Pingting; Cvetanovic, Marija; Lin, Wensheng (Frontiers in Neuroscience, 2024)
Endoplasmic reticulum-associated degradation (ERAD) is a principal quality-control mechanism responsible for targeting misfolded ER proteins for cytosolic degradation. Evidence suggests that impairment of ERAD contributes to neuron dysfunction and death in neurodegenerative diseases, many of which are characterized by accumulation and aggregation of misfolded proteins. However, the physiological role of ERAD in neurons remains unclear. The Sel1L-Hrd1 complex consisting of the E3 ubiquitin ligase Hrd1 and its adaptor protein Sel1L is the best-characterized ERAD machinery. Herein, we showed that Sel1L deficiency specifically in neurons of adult mice impaired the ERAD activity of the Sel1L-Hrd1 complex and led to disruption of ER homeostasis, ER stress and activation of the unfold protein response (UPR). Adult mice with Sel1L deficiency in neurons exhibited weight loss and severe motor dysfunction, and rapidly succumbed to death. Interestingly, Sel1L deficiency in neurons caused global brain atrophy, particularly cerebellar and hippocampal atrophy, in adult mice. Moreover, we found that cerebellar and hippocampal atrophy in these mice resulted from degeneration of Purkinje neurons and hippocampal neurons, respectively. These findings indicate that ERAD is required for maintaining ER homeostasis and the viability and function of neurons in adults under physiological conditions.